1989
DOI: 10.1073/pnas.86.9.3006
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Hoogsteen base pairs adjacent to echinomycin binding sites within a DNA duplex.

Abstract: The bisintercalation complex present between the DNA octamer [d(ACGTACGT)12 and the cyclic octadepsipeptide antibiotic echinomycin has been studied by one-and two-dimensional proton NMR, and the results obtained have been compared with the crystal structures of related DNA-echinomycin complexes. Two echinomycins are found to bind cooperatively to each DNA duplex at the CpG steps, with the two quinoxaline rings of each echinomycin bisintercalating between the C-G and A-T base pairs. At low temperatures, the ANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 25 publications
(26 reference statements)
8
88
1
Order By: Relevance
“…To more broadly examine the occurrence and sequence-specificity of transient HG bps in canonical duplex DNA, we carried out 13 C and 15 N R 1ρ NMR RD measurements targeting sugar C1′ and base C6/8 or N1/3 resonances in 20 A•T and 13 G•C bps in eight DNA duplexes that encompass a variety of sequence motifs, including (A•T) n repeats of varying length (n=2, 4, 5 and 6), a (CA) 3 repeat, a duplex sequence that forms HG bps upon binding to the antibiotic echinomycin, 1,26,27 a (CG) 3 repeat capable of forming Z-DNA, 28 and a B/Z junction forming sequence 29,30 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…To more broadly examine the occurrence and sequence-specificity of transient HG bps in canonical duplex DNA, we carried out 13 C and 15 N R 1ρ NMR RD measurements targeting sugar C1′ and base C6/8 or N1/3 resonances in 20 A•T and 13 G•C bps in eight DNA duplexes that encompass a variety of sequence motifs, including (A•T) n repeats of varying length (n=2, 4, 5 and 6), a (CA) 3 repeat, a duplex sequence that forms HG bps upon binding to the antibiotic echinomycin, 1,26,27 a (CG) 3 repeat capable of forming Z-DNA, 28 and a B/Z junction forming sequence 29,30 (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…The present study of a dumbbell shows similar buckling of the closing base pair, caused by translating timeaveraged NOE data directly into distances with neglect of equilibria between anti and syn forms. These observations raise doubts about the presence of pure syn rotamers instead of syn/high-anti/anti equilibria (at low tempera- (Kallick and Wemmer, 1991) and in echinomycin-DNA complexes (Gilbert et al, 1989;Gilbert and Feigon, 1992). Moreover, temperature-dependent line broadening was found specifically for the HI' signal of dG(10) in an RNA hairpin 5'-r(GGGCGC-UGGG-ACGCCCGUC)-3', containing the CUGGGA loop of the HIV-1 TAR element (Colvin et al, 1993).…”
Section: Why Syn ?mentioning
confidence: 92%
“…32 In several NMR-based studies, Feigon and co-workers showed that while Hoogsteen base-pairing may occur, it tended to be at the ends of the oligonucleotides studied and internal base-pairs were dynamic, alternating between open, WatsonCrick or Hoogsteen forms. 33 More recent crystal structures have again demonstrated the formation of Hoogsteen base-pairs. 34 Feigon's NMR studies also demonstrated that differences in sequence can lead to variations in cooperativity of binding.…”
Section: Biological Activity Of Echinomycinmentioning
confidence: 96%